Concise and scalable synthesis of (±)-phosphonothrixin - Yoshitaka Matsushima (Elsevier, 2021)
A concise and scalable method for the synthesis of (±)-phosphonothrixin (1), an herbicidal antibiotic containing a C–P bond, was developed. We developed a simpler and more responsible method for the synthetic precursor, epoxy alcohol 2. The synthetic route is efficient, requiring only six steps to isolate (±)-1 (18%) from the easily obtainable known epoxy alcohol 3 and can be applied to enable gram-scale synthesis.